On Development of English Reading Teaching in China: A Literature Review (2003-2023) - Zhang, Yingkun (International Journal of Education and Humanities, 2024)
Reading is the foundation of mastering a language as well as a primary instrument to obtain information. Reading teaching has always been a hot topic in English language teaching (ELT). The present study sought to trace the characteristics of existing studies on English reading teaching in China. Based on research articles in the CNKI database collected by Chinese core journals and CSSCI in the past two decades, 603 studies on English reading teaching were selected and analyzed. Firstly, the Cite Space software is used to visualize the annual number of published papers, research hotspots and research trends. Subsequently, a detailed content analysis was conducted to distil and summarise the predominant research foci in English reading instruction in China over the past twenty years. The results show that the number of published papers on reading teaching research in China increases first and then fluctuates. The evolution of research topics is discerned to encompass three distinct stages and was influenced by prevailing educational policies. The research foci mainly include three aspects: English reading teaching modes, English reading teaching strategies and English reading ability. This comprehensive review aims to map out the current research landscape, shedding light on future scholarly inquiry in English reading teaching